Thor. Vol. 3, Revelations - Cates, Donny (Marvel Worldwide, Inc., 2021)
Odin has returned! But an air of tension now sits upon the throne. Father and son. All-Father and All-Father. Odin and Thor.Is this relationship forever doomed, and what does it mean for the Ten Realms? Determined to the best leader that he can be for Asgard, Thor makes the fateful decision that he must surrender Mjolnir. But what if the hammer isn't ready to give up Thor? As all of Asgard reckons with Odin's return and the aftermath of Donald Blake's brutal attack, the God of Thunder will be rocked by revelations -- and face a shocking confrontation with the Avengers! Plus, when the Infinity Stones return, Thor and a surprising guest-star must confront an infinite destiny!